Modified Model of Prediction of Carbonation Depth Based on CEB-FIP for Concrete with Portland Cement with High Water-Cement Ratios - Flores Soto, Luis Adrian (2024)
CO2 levels in the world are constantly increasing and have generated a great impact on reinforced concrete structures causing increased carbonation. The phenomenon of carbonation causes corrosion of the reinforcing steel, therefore, reinforced concrete structures present a high risk of corrosion of its reinforcing steel causing the reduction of the useful life of the structure, or in extreme cases, a demolition must be carried out. The objective of the present study is to propose a prediction model for carbonation depth in pure concretes which are not designed for durability (w/c0.55). CEB-FIP model presents the limit of serving only for concrete with w/c<0.50, due to this, the present study proposes a model that will help as a reference to estimate the useful life of structures that are built and designed in cities where they do not are exposed to these durability conditions. The modified model for predicting the carbonation depth based on CEB-FIP in pure concrete with high w/c (0.60 and 0.72) uses the parameters of temperature, relative humidity, CO2 concentration, and water/cement ratio. The objective is to obtain the accuracy of the modified model for predicting the carbonation depth in concrete over the years. For the results, the theoretical data obtained from the modified model was used and a comparison was made with the experimental results obtained from concrete specimens tested inside an accelerated carbonation chamber to find the model's accuracy.